IPTEKS PENINGKATAN JUMLAH NASABAH PADA PT. BANK RAKYAT INDONESIA (PERSERO) TBK KCP UNIT UNSRAT MANADO - Makisanti, Eirene Lorensia; Pinatik, Sherly (Universitas Sam Ratulangi, 2018)
Bank is a people trusted financial institution which holds an important role in the economic system. Promotion is one of the most effective ways to atrract and maintain the customers. It can inform the customer about the products and influence their preferences. The strategy of sale promotion is a process of planning a company’s activities to reach its marketing goal, that is to increase the income and the sales volume, by influencing the purchase decision of the target customers. The method applied is an implementation of promotional strategy in order to increase the number of customers at Bank Rakyat Indonesia KCP Unit Unsrat Manado. The technique used was analyzing the promotional strategies utilized advertisements, face to face service, publications, and service promotions. It was found that the promotional strategies implemented increased the number of customers at Bank Rakyat Indonesia KCP Unit Unsrat ManadoKeywords : promotions, promotion strategies, increasing customers